Fikih Takwil dan Tafsir Abdullah Saeed - Jarman Arroisi (Universitas Darussalam Gontor, 2017)
In the last decade, new creativity and new awareness of some Moslem scientists who proposed the urgency to interpret al-Qur’an with new approach appeared. One of the scientists was Abdullah Saeed. He sees that there has been a tremendous change in human history. Therefore, he thinks there should be efforts to apply contextual approach of interpreting al-Qur’an. Interpretive approach to the context in question is the interpretation of the trust that the teaching model of the Koran today can be applied by several methods in accordance with the conditions, so that the meaning of the content of the Qur’an that can lead mankind. Model interpretation of this context approach can be implemented through four stages; face word in the text, criticize and analyze the language and considering the context of the letter, meaning that first received and then continued by looking at the social situation and consider the meaning of what is needed at this time. With critical analytical method, this paper tries to explain what and how true interpretation Saeed context approach was realized. Although the idea of true interpretation is not the first time appeared nor purely of itself, but with all the advantages and disadvantages that exist, the proposal was interesting to be observed.